Offering Sharia Securities Through Technology Based Crowdfunding Services Based on Sharia Principles According to MUI Fatwa - Bianda, Ryan; Gunaepi, Aang; Misbakul Munir, Muhammad (Riviera Publishing, 2023)
This study aims to provide an understanding to the public regarding sharia securities offerings to avoid losses through crowdfunding services as organizers of legal entities that provide, manage, and operate crowdfunding services. This study used a qualitative method by reviewing related literature on information technology-based crowdfunding services based on sharia principles. Fatwa of the National Sharia Council (DSN) MUI FATWA NO: 140/DSN-MUI/VIII/2021 concerning Information Technology-Based Financing Services based on Sharia Principles explaining that sharia securities services through crowdfunding must avoid usury, graham, and deadlines. This research makes investing in sharia securities in technology-based crowdfunding services based on sharia principles easier. This research has implications that it can make a significant contribution in protecting investors oriented to sharia principles, can have an impact on increasing public trust in crowdfunding services provided by legal entities and has an impact on increasing access to Islamic finance for individuals and groups who want to fund or finance projects in accordance with sharia principles.